Efficacy of the therapeutic use of video games on the depressive state of stroke patients: Protocol for systematic review and meta-analysis. - Patricia Blázquez-González; Rubén Mirón-González; Alejandro Lendínez-Mesa; María Nieves Moro-Tejedor; José Luis Cobo-Sánchez; Noelia Mancebo-Salas; María Teresa Camacho-Arroyo; Leyre Rodríguez-Leal; Raquel Luengo-González (PLoS ONE, 2022)
Aim To assess the effects of virtual reality (VR) on the depressive state of patients with stroke admitted to neuro-rehabilitation units. Design: Systematic review and meta-analysis protocol. Methods Randomized Controlled Trials (RCTs) focusing on the effects of virtual reality on depressive state as a primary outcome will be included. Grey literature and the following databases will be consulted: PubMed, Cinahl, PsycInfo, Scopus, Embase, Cochrane Library and Web of Science. The recently revised Cochrane risk of bias tool will be used to assess the quality of included studies. Data will be extracted and meta-analyses will be performed within the specific condition of the emotional state of stroke patients admitted to neurorehabilitation units. Meta-regression and subgroup analyses will be used to identify effective modes and patterns of therapy delivery. The approach of assessment, development and evaluation of recommendations will be applied to reach a convincing conclusion. Discussion An accurate, transparent and standardized review process is expected to provide recommendations on the use of VR technology in the healthcare of stroke patients. Impact Emotional difficulties are common after stroke and have an impact on rehabilitation outcome. VR seems to have an important role in the treatment and depression in neurological patients, as it is able to improve levels of well-being, coping strategies and social relationships. The systematic review may contribute to a more convincing and specific conclusion compared to existing studies of this type. Trial registration Systematic review registration: CRD42022303968.